Getting started with Hibernate 3 - Elliott, James (O'Reilly short cuts., 2006)
Hibernate has clearly arrived. Are you ready to benefit from its simple way of working with relational databases as Java objects? This PDF updates the introductory material from the award-winning Hibernate: A Developer's Notebook to teach you how to jump right in and get productive with the current release of Hibernate. You'll be walked through the ins and outs of setting up Hibernate and some related tools that make it easier to use--and that may give you new ideas about how to store information in your Java programs. In short, this PDF gives you exactly the information you need to start using Hibernate today.